2015
DOI: 10.1007/s11920-015-0593-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging and Sexual Behavior: Identification of Regional and Functional Differences

Abstract: The neuroanatomical correlates of human sexual desire, arousal, and behavior have been characterized in recent years with functional brain imaging techniques such as magnetic resonance imaging (MRI) and positron emission tomography (PET). Here, we briefly review the results of functional neuroimaging studies in humans, whether healthy or suffering from sexual disorders, and the current models of regional and network activation in sexual arousal. Attention is paid, in particular, to findings from both regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 62 publications
1
39
0
Order By: Relevance
“…However, reduced rich club coefficient was found in both networks of pED, which suggested that disrupted global communication of brain had a key role in the pathophysiology of pED. In addition, the inefficient integration among regions in charge of emotional, cognitive, motivational, and autonomic components of the human brain (Cheng et al, 2015) might be related to the effects of abnormal psychological factors on erectile function of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, reduced rich club coefficient was found in both networks of pED, which suggested that disrupted global communication of brain had a key role in the pathophysiology of pED. In addition, the inefficient integration among regions in charge of emotional, cognitive, motivational, and autonomic components of the human brain (Cheng et al, 2015) might be related to the effects of abnormal psychological factors on erectile function of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increased activation in the frontal brain areas plays an important role in the sustained visual attention to motivationally relevant stimuli, which lead to increased response inhibition of sexual arousal and erection responses (Sennwald et al, 2016). Activation is reported in the frontal cortex in response to sexually arousing film clips (Cheng et al, 2015). The pre-frontal cortex is also implicated in ejaculation control (Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The pre-frontal cortex is also implicated in ejaculation control (Yang et al, 2018). A remarkable decrease of function throughout the pre-frontal cortex is found during ejaculation (Cheng et al, 2015). In addition, the disruption of frontal brain areas may lead to an state of hypersexuality by the reduced inhibitory effect on sexual behavior (K€ uhn & Gallinat, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amygdala is essential for emotional processes (Madan et al, 2017 ); meanwhile, it is extensively interconnected with the prefrontal cortex (Gold et al, 2015 ), which is responsible for the cognitive aspects of emotional responses. In addition, prior model relates some brain regions to distinct components of SA, including cognitive, motivational, autonomic, and emotional components (Redouté et al, 2000 ; Ferretti et al, 2005 ; Cheng et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%